2017
DOI: 10.1161/jaha.116.003892
|View full text |Cite
|
Sign up to set email alerts
|

International Variation in Outcomes Among People with Cardiovascular Disease or Cardiovascular Risk Factors and Impaired Glucose Tolerance: Insights from the NAVIGATOR Trial

Abstract: BackgroundRegional differences in risk of diabetes mellitus and cardiovascular outcomes in people with impaired glucose tolerance are poorly characterized. Our objective was to evaluate regional variation in risk of new‐onset diabetes mellitus, cardiovascular outcomes, and treatment effects in participants from the NAVIGATOR (Nateglinide and Valsartan in Impaired Glucose Tolerance Outcomes Research) trial.Methods and Results NAVIGATOR randomized people with impaired glucose tolerance and cardiovascular risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…In randomized clinical trials such as the NAVIGATOR study, Latin American participants with glucose intolerance had an increased risk of cardiovascular death (HR 2.68, 95% CI 1.82–3.96) and composite cardiovascular outcome (HR 1.48, 95% CI 1.15–1.92). When the data are recorded in the context of a clinical trial, they may not reflect the real characteristics of the population by the specified selection criteria [14]. In the PURE study identified that although risk-factor burden may be lower in LMIC, the risk of cardiovascular events was much higher [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In randomized clinical trials such as the NAVIGATOR study, Latin American participants with glucose intolerance had an increased risk of cardiovascular death (HR 2.68, 95% CI 1.82–3.96) and composite cardiovascular outcome (HR 1.48, 95% CI 1.15–1.92). When the data are recorded in the context of a clinical trial, they may not reflect the real characteristics of the population by the specified selection criteria [14]. In the PURE study identified that although risk-factor burden may be lower in LMIC, the risk of cardiovascular events was much higher [19].…”
Section: Discussionmentioning
confidence: 99%
“…The use of statins in the LMIC is low in comparison with the HIC [28]. In the NAVIGATOR study, was reported that patients in Latin America used fewer therapies for prevention of cardiovascular events, such as aspirin (32% versus 47% in North America and 35% in Europe), lipid-lowering therapies (28% versus 55% in North America and 35% in Europe), and ACEIs (4% versus 9% in North America and 8% in Europe) [14]. In the TECOS study, low use of statins and aspirin in Latin America compared to North America was reported [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such expensive and complex strategies produced less satisfactory results in clinical trials. Further, epidemiological variations in the therapeutic outcomes have also been reported …”
Section: Introductionmentioning
confidence: 99%